The development of an âin vivo assay techniqueâ as a tool for measuring protective immune responses of vaccine against myiasis in sheep - Partoutomo, S.; ., Sukarsih; Satria, E.; Eisemann, C.H. (Indonesian Animal Sciences Society, 1998)
An âin vivo assay techniqueâ is urgently needed for measuring protective immune effects of a myiasis vaccine in sheep. Such a technique is being developed simultaneously with the development of a vaccine against myiasis caused by the screwworm fly Chrysomya bezziana under a collaborative project undertaken by Balitvet, ITB and CSIRO (Australia) and funded by ACIAR. Experiments were conducted in naive sheep. C. bezziana larvae were allowed to develop on abraded skin in aluminium rings which had been attached to the sheep by means of a glue (Aibon) on the day prior to infection. Rings were arranged on clipped areas close to the mid line of the sheepâs back, two rings on the right side and two rings on the left. Four trials were performed, involving studies on the effects of including wet sponges in the rings to maintain humidity (Trial 1); the effects of sponge and blended meat as counting and transferring media during infection (Trial 2); the effects of the repellants citronella, eucalyptus oil and neem extract in assisting the recovery of larvae (Trial 3); and the effects of the reducing the infective dose from 50 to 25 1st instar larvae/ring and using a fine brush for counting and transferring larvae instead of using a forceps as in the previous groups (Trial 4) on the larval recovery rates (LRR). The results indicated that the inclusion of wet sponges in the rings, the use of sponge and blended meat as counting and transferring media during infection, and the application of repellants all increased the LRR to some extent; however, variations among individual rings remained high. On the other hand, the reduction of infective dose of larvae from 50 to 25 1st instar larvae/ring and using a fine brush for counting and transferring larvae sharply increased the LRR while substantially decreasing the coefficient variations. Key words : Myiasis, Chrysomya bezziana, larval recovery rate